Combination of HGF and IGF-1 promotes connexin 43 expression and improves ventricular arrhythmia after myocardial infarction through activating the MAPK/ERK and MAPK/p38 signaling pathways in a rat model - Yao, Jierong; Ke, Jianting; Zhou, Zhijuan; Tan, Guangyi; Yin, Yuelan; Liu, Mao; Chen, Jian; Wu, Wei (Cardiovascular Diagnosis and Therapy; Vol 9, No 4 (August 28, 2019): Cardiovascular Diagnosis and Therapy, 2019)
Background: In this study, we hypothesized that the combination of hepatocyte growth factor (HGF) and insulin-like growth factor-1 (IGF-1) alters the expression of connexin 43 (Cx43) and results in a reduced frequency of induced ventricular arrhythmia in rats after myocardial infarction (MI) and explored the preliminary mechanisms involved. Methods: Cardiomyocytes were cultured in vitro in medium with PBS, HGF, IGF-1, GFs (HGF + IGF-1), HGF + p38 inhibitor, HGF + ERK inhibitor, IGF-1 + p38 inhibitor or IGF-1 + ERK inhibitor. The expression of Cx43 was tested by real-time PCR and Western blotting after 48 hours. MI was induced in 48 male Sprague-Dawley rats. The rats were randomly divided into four groups and received an injection of PBS, HGF, IGF-1 or GFs into the infarct border zone two weeks after MI. Six weeks after injection, the expression levels of Cx43 and programmed stimulation-induced ventricular arrhythmias were examined. Results: In vitro, the expression of Cx43 mRNA and the Cx43 protein in cardiomyocytes was higher in the HGF, IGF-1, and GFs groups than in the PBS group. GFs had a combinatorial effect on the Cx43 mRNA level but not on the Cx43 protein level. There was a significant reduction in Cx43 mRNA and Cx43 protein levels in the IGF-1 + p38 inhibitor group and IGF-1 + ERK inhibitor group compared to the IGF-1 group. In vivo, programmed stimulation significantly decreased the frequency of ventricular arrhythmia in the GFs, HGF and IGF-1 groups, and this effect was accompanied by increased immunohistochemical staining for Cx43, myocardial Cx43 protein levels and Cx43 mRNA levels in the infarct border zone of the left ventricle compared with those in the PBS group. The combinatorial effect of GFs on Cx43 expression was only observed at the mRNA level. Conclusions: Both HGF and IGF-1 enhanced the expression of Cx43 and improved induced ventricular arrhythmia in rats with MI. Both synergistic and antagonistic effects of HGF and IGF-1 were not observed. In addition, IGF-1 may function through the MAPK/p38 and ERK1/2 signaling pathways to regulate Cx43 expression.